Analisis Beban Runtuh dan Evaluasi Lubang Bukaan Berdasarkan Metode Rock Mass Rating dan Q-System pada Tambang Bawah Tanah CV. Bara Mitra Kencana, Kota Sawahlunto, Sumatera Barat - Ilep Prengki; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2018)
Abstract.The excavation of a underground rock mass resulting a change in the balance of rock conditions such as the occurrence of rock collapse and changes in the dimensions of tunnel as a result of the displacement of the voltage distribution. It is desirable to have a good geotechnical analysis to provide an appropriate treatment of rocks excavated. This research was conducted to determine rock mass class, rock strength at BMK 34 CV Bara Mitra Kencana. Classification of  rocks mass with RMR system And Q-System FK potential of wedge  using unwedge software. From the measurement of several parameters of RMR method,  RMR value of  48 ( Coal) and  60 (Sillstone) is obtained where as rock mass class III (fair rock), based on  the Q-System obtained a value of 14 in class II for coal and 4 Class III for Sillstone. Based on the RMR-system classification, the value for span maximum is 3 m with a collapse time of 110 hours and the value of the load collapses is 1,56 tons / m2. Based on the Undwedge Software processing, there was an increase in FK values for both methods, Based  on Support RMR Ground from 1,907 to 2,939 and Based on Ground Support Q-System from 1,907 to 2,078.Keywords : Underground, Rock Mass Ratting, Q-System, Safety Factor, Ground Support